The LAMP-CRISPR-Cas13a technique for detecting the CBASS mechanism of phage resistance in bacteria - Ortiz-Cartagena, Concha; Fernández-Grela, Patricia; Armán, Lucia; Blasco, Lucía; Pablo-Marcos, Daniel; Bleriot, Inés; Fernández-García, Laura; Ibarguren-Quiles, Clara; Fernández-Cuenca, Felipe; Barrio-Pujante, Antonio; Aracil, Belén; Calvo-Montes, Jorge; et al. (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance (AMR) is a major public health threat, driving the need for alternative treatments such as phage therapy. However, bacterial defense mechanisms, often regulated by the quorum sensing (QS) network and encoded in genomic islands (GIs), can generate phage-resistant mutants. Understanding these resistance mechanisms is essential for optimizing phage therapy.MethodsThis study analyzed 48 Klebsiella pneumoniae strains to identify pathogenicity islands (PAIs) containing anti-phage defense (APD) proteins. We constructed a knockout strain lacking the cyclase gene from the type II CBASS defense systems present in PAIs to investigate QS regulation and its role in cell viability. The LAMP-CRISPR-Cas13a technique was used to confirm gene knockout and to detect the main cyclase in type I CBASS systems, i.e., APECO1.ResultsA total of 309 pathogenicity islands (PAIs), containing 22.1% of anti-phage defense (APD) proteins, were identified. Type I and II CBASS APD systems were also detected in the genome of the 48, K. pneumoniae strains, and only two type II CBASS systems were located in PAIs. Alluding to these defense mechanisms, the QS revealed to be involved in the regulation of the type II CBASS systems contained in PAIs. Finally, the LAMP-CRISPR-Cas13a technology successfully detected the main cyclases habored in type I and II CBASS systems, respectively.DiscussionThe study findings highlight the regulatory role of the QS network in APD systems. Notably, this is the first study to develop an innovative biotechnological application for the LAMP-CRISPR-Cas13a rapid-technique (<2 h), thereby helping to optimize phage therapy by detecting bacterial resistance mechanisms and predicting the potential inefficacy of therapeutic phages and thus improving patient prognosis.